Smart sensor simulator / Yogeswari Jayaraman - Yogeswari, Jayaraman (2005)
As part of fulfillment of the requirements for the Bachelor of Computer Science Degree, we are required to do a thesis on a selected title. My thesis title is Smart Sensor Simulator. This project will be on smart sensors that are based on IEEE 1451.2 standard Smart sensors are replacing the traditional sensors that were once used. The IEEE 1451 standards specify set of common communication interfaces to standardize the connectivity of transducers to microprocessor, instrumentation systems, and networks. This is done by specifying different standards that address the various aspects of the development of smart networked transducers. The scope of my thesis was narrowed down to doing a simulation of the electronic data sheet that associated with the smart sensors and serves as a test bench for those who want to enhance the project.